Inspection Control and the Environmental Protection - Milkov, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Environmental protection is the task of many administrative bodies, but the activity of the environmental inspection is of special importance. According to the Law on Environmental Protection, inspection`s tasks in this area belong to the competence of republican bodies, ie. Ministry of Agriculture and Environmental Protection. Autonomous province and local self-government have only delegated competence in this field, under condition that this is explicitly regulated in special laws. Environmental inspection`s activity consists in preventive actions, certain prior - preparatory activities and the audit itself. In addition, following the intervention of the Inspector issue of the control may be corrective or repressive. According to the Law on Inspection Control and the Law on Environmental Protection, the inspectors have a number of powers and responsibilities, which enable them to ensure the lawful and proper conduct of individuals and legal entities.